The kinetics and adsorption equilibrium of the removal of textile dyes from aqueous solutions by a bio-adsorbent produced from solid cassava (Manihot Esculenta Crantz) waste - Dias, Rafael; José Guerreiro de Faria, Lênio; Cruz Martelli, Marlice; do Socorro Barros Brasil, Davi (Electronic Journal "Fórum Ambiental da Alta Paulista", 2024)
The chemical contamination of wastewater with textile dyes and the excessive generation of agro-industrial solid waste are the two issues addressed in this study. A possible solution to both problems is the production of activated carbon from solid cassava waste to remove the textile dyes, such as methylene blue, from wastewater. This study focused on the synthesis of activated carbon from cassava pulp for the adsorption of methylene blue. Therefore, the activated carbon precursor was characterized to analyze the total protein (0.51%), moisture (83.40%), oil (0%), and carbohydrate (16.10%) content. Kinetics and equilibrium tests were conducted using a fixed bed with 120 mg/L of dye and 0.01 g of carbon. The adsorption kinetics indicated a good fit to the intraparticle diffusion model, whereas the adsorption equilibrium sufficiently aligned with the Langmuir model. The activated carbon produced from the cassava pulp yielded highly satisfactory results under the experimental conditions evaluated in this study, thus may be used as an effective and low-cost bio-adsorbent to remove methylene blue dye from aqueous solutions. Accordingly, our study provides a potentially valuable solution to textile dye contamination and agro-industrial waste management problems while simultaneously utilizing a cassava by-product for beneficial and sustainable purposes.